Immunochemical Detection of Oxalate Monoalkylamide, an Ascorbate-derived Maillard Reaction Product, in the Human Lens - Nagaraj, Ram H.; Shamsi, Farrukh; Huber, Birgit; Pischetsrieder, Monika (Febs Letters, 1999)
Carbohydrates with reactive aldehyde and ketone groups can undergo Maillard reactions with proteins to form advanced glycation end products. Oxalate monoalkylamide was identified as one of the advanced glycation end products formed from the Maillard reaction of ascorbate with proteins. In these experiments, we have analyzed human lens proteins immunochemically for the presence of oxalate monoalkylamide. Oxalate monoalkylamide was absent in most of the very young lenses but was present in old and cataractous lenses. The highest levels were found in senile brunescent lenses. Incubation experiments using bovine lens proteins revealed that oxalate monoalkylamide could form from the ascorbate degradation products, 2,3-diketogulonate and L-threose. These data provide the first evidence for oxalate monoalkylamide in vivo and suggest that ascorbate degradation and its binding to proteins are enhanced during lens aging and cataract formation.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.immuno
Keywords: Ascorbate degradation; Human lens; Maillard reaction; Oxalate monoalkylamide